Epidemiology of African swine fever virus - Costard, Solenne; Mur, L.; Lubroth, J.; Sánchez Vizcaino, J.M.; Pfeiffer, Dirk U. (Elsevier, 2013)
African swine fever virus used to occur primarily in Africa. There had been occasional incursions into Europe or America which apart from the endemic situation on the island of Sardinia always had been successfully controlled. But following an introduction of the virus in 2007, it now has expanded its geographical distribution into Caucasus and Eastern Europe where it has not been controlled, to date. African swine fever affects domestic and wild pig species, and can involve tick vectors. The ability of the virus to survive within a particular ecosystem is defined by the ecology of its wild host populations and the characteristics of livestock production systems, which influence host and vector species densities and interrelationships. African swine fever has high morbidity in naïve pig populations and can result in very high mortality. There is no vaccine or treatment available. Apart from stamping out and movement control, there are no control measures, thereby potentially resulting in extreme losses for producers. Prevention and control of the infection requires good understanding of its epidemiology, so that targeted measures can be instigated.